2020
DOI: 10.1155/2020/2173765
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Gender and Resistance to Change on the Adoption of Big Data Analytics in Healthcare

Abstract: The big data analytics (BDA) has dragged tremendous attention in healthcare organizations. Healthcare organizations are investing substantial money and time in big data analytics and want to adopt it to get potential benefits. Thus, this study proposes a BDA adoption model in healthcare organizations to explore the critical factors that can influence its adoption process. The study extends the technology acceptance model (TAM) with the self-efficacy as an external factor and also includes gender and resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 85 publications
2
28
0
1
Order By: Relevance
“…This finding is consistent with previous studies, which suggest that readiness to accept change is crucial to individuals' success in adapting to new ways of working or behaving (e.g. Shahbaz et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous studies, which suggest that readiness to accept change is crucial to individuals' success in adapting to new ways of working or behaving (e.g. Shahbaz et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, resistance to change was found to moderate the association between different cognitive and behavioral variables and the adoption of new technology (Huang, 2015). For example, Shahbaz et al (2020) studied employees' intentions to use big data analytics in health-care organizations and found that the higher their resistance to change, the weaker the association was between intention to adopt change and the adoption of actual change. Therefore, although previous work has addressed the relation between resistance to change and the adoption of new technology, no research to date has examined the effect of resistance to change on success in online teaching.…”
Section: Resistance To Changementioning
confidence: 99%
“…In the present era of big data, input data from all available sources, such as social media (e.g., social, electronic, and mobile commerce websites), sales forums, competitor data, and other stakeholder data, are mandatory for ensuring the efficient output of analyzed information [21][22][23][24]. In the management of organizational sales performance, BDA can store and analyze big data of massive amounts, variety, and velocity from all possible resources, including social commerce sites, electronic commerce sites, mobile commerce sites, competitors, substitute products or service organizations, and decision-making [25][26][27][28]. erefore, BDA may solve the existing sales force problems, especially in pharmaceutical organizations.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Even though BDA has seen rapid growth in recent years (see Fig. 6), the study by Shahbaz et al [129] revealed no gender balance in the adaptation of BDA in most industries. That is, males, as compared with females, are dominant towards the positive intent to use BDA.…”
Section: Prospects For Future Studiesmentioning
confidence: 99%